Toxicity of diatom Pseudo-nitzschia (Bacillariophyceae) analyzed using high performance liquid chromatography (HPLC) - Lim, HC; Su, S.N.P; Mohamed-Ali, H.; Kotaki, Y.; Leaw, CP; Lim, PT (Journal of Science and Technology in the Tropics, 2010)
Amnesic shellfish poisoning (ASP) is a type of shellfish poisoning due to the consumption of shellfish mollusks contaminated with domoic acid (DA). The toxin was first reported in the chain-forming pennate diatom, Pseudo-nitzschia and subsequently in other diatom species. In this study, clonal cultures of Pseudo-nitzschia were established from plankton samples collected from Sarawak and Sabah coastal waters. Clonal cultures were maintained in SWII medium with the addition of silicate at 25°C, 30 PSU and under 12:12 light-dark photoperiod. Fifteen milliliters of late exponential phase cultures were collected for toxin analysis and subsamples were taken for cell count. Cellular toxin was extracted by boiling in medium at 100°C for 5 minutes. The extracts were filtered to remove cell debris before being analyzed with HPLC using standard domoic acid, isodomoic A and B as reference toxins. All the 32 strains of Pseudo-nitzschia sp. analyzed in this study showed the absence of peaks corresponding to the three ASP toxins. This implies that non-toxic strains of Pseudo-nitzschia sp. are common in Malaysian waters. Further study will be carried out to include more strains along the coastal waters of Borneo as well as selected sites with shellfish farming activities in Peninsula Malaysia.